2018
DOI: 10.1111/sms.13072
|View full text |Cite
|
Sign up to set email alerts
|

Technical determinants of biathlon standing shooting performance before and after race simulation

Abstract: The aim of this study was to identify performance-determining factors in biathlon standing shooting in rest and after intense exercise. Eight Finnish national- and nine junior-team biathletes participated in the study. Participants fired 40 resting shots (REST) and 2 × 5 competition simulation shots (LOAD) after 5 minutes of roller skiing at 95% of peak heart rate. Hit percentage, aiming point trajectory and postural balance were measured from each shot. Cleanness of triggering (ATV, movement of the aiming poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 21 publications
(80 reference statements)
6
67
0
1
Order By: Relevance
“…Moreover, in the descriptive results it is possible to notice the fact that increasing intensity of the physical load corresponds with increased movement of the rifle, respectively worse rifle stability. Consequently, the increased heart rate correlates with worse targeting stability as has been confirmed in previous researches of several authors (Gallicchio et al, 2018;Haug, 2018;Ihalainen et al, 2018;Laaksonen et al, 2018;Sattlecker et al, 2015;Sattlecker et al, 2017;Vonheim, 2012;Žák et al, 2017). In our study, the statistical significance was only showed in comparing parameters of dynamics rifle stability during targeting in resting conditions against these parameters in exercise Intensity 3 in the women group.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Moreover, in the descriptive results it is possible to notice the fact that increasing intensity of the physical load corresponds with increased movement of the rifle, respectively worse rifle stability. Consequently, the increased heart rate correlates with worse targeting stability as has been confirmed in previous researches of several authors (Gallicchio et al, 2018;Haug, 2018;Ihalainen et al, 2018;Laaksonen et al, 2018;Sattlecker et al, 2015;Sattlecker et al, 2017;Vonheim, 2012;Žák et al, 2017). In our study, the statistical significance was only showed in comparing parameters of dynamics rifle stability during targeting in resting conditions against these parameters in exercise Intensity 3 in the women group.…”
Section: Discussionsupporting
confidence: 64%
“…The majority of researches that have been presented so far were chiefly focused on the stability of the standing shooting position, the stability of the rifle during targeting, triggering and the dependence of the above mentioned parameters on the shooting success (Gallicchio et al, 2018;Haug, 2018;Ihalainen et al, 2018;Laaksonen et al, 2018;Sattlecker et al, 2015;Sattlecker et al 2017;Žák et al, 2017). Results of specific researches confirmed the dependence between the intensity of the physical load and the athlete´s postural stability in the standing shooting position, especially in anterior-posterior axis (Gallicchio et al, 2018;Haug, 2018;Ihalainen et al, 2018;Laaksonen et al, 2018;Sattlecker et al, 2015;Sattlecker et al, 2017;Vonheim, 2012;Žák et al, 2017). Høydal and Nord (2017) presented the importance of heart rate monitors during training by junior biathletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it might be that more detailed analysis of the spread of hits would reveal other relationships to exercise intensity than in our study. Interestingly, it has been suggested that the most important parameters of biathlon shooting technique are movement of the rifle in the vertical direction and cleanness of triggering (i.e., movement of the rifle 0.2-0.0 s before triggering; Ihalainen et al, 2018). This study additionally found that these parameters were negatively affected by high intensity exercise in both junior and elite biathletes, but that elite biathletes scored better than juniors on these technique parameters (Ihalainen et al, 2018).…”
Section: Shooting Performancementioning
confidence: 52%
“…Interestingly, it has been suggested that the most important parameters of biathlon shooting technique are movement of the rifle in the vertical direction and cleanness of triggering (i.e., movement of the rifle 0.2-0.0 s before triggering; Ihalainen et al, 2018). This study additionally found that these parameters were negatively affected by high intensity exercise in both junior and elite biathletes, but that elite biathletes scored better than juniors on these technique parameters (Ihalainen et al, 2018). Altogether this indicates that biathletes' shooting technique is altered more by intense exercise than what can be seen on shooting performance measured as number of hits during a competition.…”
Section: Shooting Performancementioning
confidence: 99%